What are clusters and how can they be understood? : a systematic review of literature - Hasnain, Tehmina F. (Cranfield University, 2011)
The idea of business clusters has been examined and studied since the beginning of the 19th century with claims being made that they exist in every part of the world, in some form or the other. The restructuring and flexibly of industry has resulted in inter-firm relationships taking higher importance and becoming more prominent, with associated benefits clustering such as increased productivity, entrepreneurship and innovation being recognized as key sources of competitive advantage both for the firm and the region as a whole. Despite the importance, the cluster phenomena is still misunderstood and surrounded by lack of clarity which leads to its credibility being questioned. Researchers claim that for the cluster concept to become a valid and a worthwhile subject of analysis and policy, it must be defined and understood more clearly than it is at present. . However, this is not a simple task as the criterion which is to be used to define clusters is difficult to decide on due to the fact that there are many different ways of studying and using the term. This paper aims to provide a better model for understanding and analysing clusters by exploring the question of “what are clusters and how can they be understood” through the systematic review process. The process involves (1) identifying all relevant published and unpublished evidence (2) selecting studies for inclusion (3) assessing the quality of the studies (4) synthesising findings in an unbiased way (5) interpreting and presenting the findings in an unbiased and impartial way. The systematic review results in descriptive findings that highlight the characteristic sand structure of the literature and also allow a reflection on the main area of enquiry. These findings also set the background for the conceptual analysis which is based on the proposition that the study of clusters is multidimensional. By assessing, combining and analysing the results of the systematic review process, the descriptive and conceptual findings are given meaning and placed into context. This leads to gaps being identified in literature which results in future research areas being proposed for the PhD.